Why Do Small‐Scale Irregularities Migrate Beyond the Equatorial Plasma Bubble? - Yuanlin Jia; Gang Chen; Jiyao Xu; Chunxiao Yan; Shaodong Zhang; Lianhuan Hu; Wei Jia; Min Zhang; Wanlin Gong; Yimeng Xu; Pengfei Hu; Muchen Yang (Geophysical Research Letters)
Abstract F‐region Field‐Aligned Irregularities (FAIs) observed by the Hainan Coherent Scatter Phased Array Radar (HCOPAR) and the Equatorial Plasma Bubbles (EPBs) observed by four All‐Sky Airglow Imagers (ASAIs) in the night of 4 November 2023 were compared. The spatiotemporal distribution of the FAIs was nearly consistent with that of the EPBs. However, certain FAIs were located outside the EPBs. Oblique band‐like echoes extended beyond the EPBs between 12:30 and 13:30 UT, with the opposite line‐of‐sight velocities of the echo components above and below. Electrostatic reconnection between adjacent bubbles was considered a driving mechanism for the irregularities extending outward. Between 14:30 and 15:30 UT, certain FAIs were located outside the eastern wall of the bubble. The upward electric field component in the westward tilted bubble will transport the plasma from eastern wall and make the high density gradient region extend outside the bubble, and the irregularities appeared due to the polarization electric field extending outside the bubble.